A survey of veterinarian mental health and resilience in Ontario, Canada - Best, Colleen O. (Can Vet J, 2020)
Our goal was to help address a lack of mental health research on Canadian veterinarians through estimation of the prevalence of depression, anxiety, compassion fatigue, burnout, and resilience in veterinarians in Ontario. We conducted a cross-sectional study using an online survey that investigated demographics, mental health, self-reported overall health, and satisfaction with sources of support. Validated, psychometric scales were used to measure depression, anxiety, burnout, compassion fatigue, and resilience. The mental health indices of participating veterinarians were in line with those of veterinarians in other regions, and reflective of poorer mental health compared to the general population. The scores for females tended towards poorer mental health relative to males. Reported levels of burnout and secondary traumatic stress were of particular concern. These results can be used to support evidence-based interventions to help veterinarians and veterinary students build their resilience so that they may better thrive in the face of occupational stresses.